Seed and seedling ecology of tree species in neotropical secondary forests: management implications - Guariguata, Manuel R. (2000)
Inter-specific patterns of seed longevity in the soil, germination, and survival and growth of transplanted seedlings under closed canopy of nine trees, Cordia alliodora, Hampea appendiculata, Jacaranda copaia, Laetia procera, Rollinia microsepala, Simarouba amara, Stryphnodendron microstachyum, Trichospermum grewiifolium and Vochysia ferruginea, common in secondary forest stands in wet, lowland Costa Rica, are described. Longevity of experimental seed cohorts differed markedly among species, from <3 mo (Cordia, Hampea, Simarouba, Vochysia), to >1 yr (Stryphnodendron). Similarly, germination of recently dispersed seeds in the understorey ranged from 0% in Laetia to >75% in Cordia and Vochysia. In contrast, seedling survival was uniformly low (<10% survival one year after transplanting except for Stryphnodendron, which showed ~ 20% survival). Implications of these findings for the management of secondary forest stands for timber production vary. All the species require nearly complete canopy opening to regenerate. Some species germinate well in the shade and can be managed at the seedlings stage by opening up the canopy a few months after germination (e.g., Cordia, Simarouba, Vochysia). Species showing little or no germination under closed canopy (e.g., Jacaranda, Laetia, Rollinia) need canopy removal to germinate adequately. Any canopy manipulation must be performed within 6 months. Site preparation may be necessary to control herbs and shrubs. The study results suggest that ecological classifications of trees solely based on light preferences for stem growth may fail to account for important differences among species in their regeneration mode. This is of particular importance for refining silvicultural guidelines in neo-tropical secondary forests.